Advancing Applications of Black Phosphorus and BP‐Analog Materials in Photo/Electrocatalysis through Structure Engineering and Surface Modulation - Teng Yin; Liyuan Long; Xian Tang; Meng Qiu; Weiyuan Liang; Rui Cao; Qizhen Zhang; Dunhui Wang; Han Zhang (Advanced Science, 2020)
Abstract Black phosphorus (BP), an emerging 2D material semiconductor material, exhibits unique properties and promising application prospects for photo/electrocatalysis. However, the applications of BP in photo/electrocatalysis are hampered by the instability as well as low catalysis efficiency. Recently, tremendous efforts have been dedicated toward modulating its intrinsic structure, electronic property, and charge separation for enhanced photo/electrocatalytic performance through structure engineering. Simultaneously, the search for new substitute materials that are BP‐analogous is ongoing. Herein, the latest theoretical and experimental progress made in the structural/surface engineering strategies and advanced applications of BP and BP‐analog materials in relation to photo/electrocatalysis are extensively explored, and a presentation of the future opportunities and challenges of the materials is included at the end.